ANGIOSPERMIC PLANT RESOURCES AND FOLK USES IN DISTRICT KARAK, KHYBER PAKHTUNKHWA, PAKISTAN - N. Akhtar; A. Siddique; M. Anwar (Journal of Animal and Plant Sciences, 2018)
Ethnobotanical survey of angiosperms was undertaken in district Karak KP, Pakistan during March, 2010 through April, 2011.The aims and objectives of the study were to document the indigenous knowledge of plants particularly medicinal, fuel, timber, vegetables, ornamentals and fruit plants. A total of 88 genera and 103 species belonging to 43 families were collected from district Karak, KP, Pakistan. Out of 103 plant species, 76 species (74%) were herbs, 15 species (14%) were trees and 12 species (12%) were shrubs. Among these 103 plants, 70 (6 7.9%) plants are used as a fodder for cattle, 52 ( 50.4%) medicinal, 38( 36.8%) fuel, 8 (7.7%) timber, 8 (7 .7%) vegetables, 7 ( 6.8%) ornamental and 4 ( 3.8%) as edible fruits. Out of these, 6 (5.8%) used as a hedge plants and 10 ( 9.7%) used for miscellaneous purposes. is the scientific study of the traditional knowledge and
Keywords: Ethnobotany; Flora; Medicinal plants; Karak; Pakistan.